Application of Cloud Computing Technology in Computer Data Processing - Ma, Ruhui (Journal of Artificial Intelligence and Information, 2025)
In recent years, cloud computing in China has developed rapidly. In the process of continuous progress, it provides a good platform for computer data processing work, plays a role in promoting the progress of computer technology, and has a wide range of applications, which can enhance the level of computer data processing, which is of great significance. Based on this, this paper studies and analyzes the application value of cloud computing in computer data processing, and puts forward some suggestions to enhance the effect of data processing.